Analisis Miskonsepsi Turunan Fungsi pada Buku Matematika SMA : Definisi Turunan, Visual Grafik, dan Contoh Soal - Nazwa Azzahra; Putri Isnaini; Sabrina Nur Karimah Nst; Chelsea Natalia; Wingston Leonard Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Penelitian ini bertujuan untuk menganalisis miskonsepsi yang muncul dalam buku teks Matematika SMA pada topik turunan fungsi, khususnya terkait dengan definisi turunan, representasi visual melalui grafik, serta contoh soal yang disajikan. Turunan merupakan. This research aims to analyze the misconceptions that arise in high school mathematics textbooks on the topic of function derivatives, specifically regarding the definition of derivatives, visual representation through graphs, and the example problems presented. Derivatives are a fundamental concept in calculus that requires not only procedural skills but also a deep conceptual understanding.The analysis shows that some books still present the definition of a derivative rigidly without connecting the meaning of a limit to the instantaneous rate of change. In the aspect of graphical visuals, there is a tendency to display illustrations that are inconsistent with the formal definition, making it difficult for students to connect the function graph with its derivative graph. Additionally, example problems often only emphasize mechanistic techniques (using quick derivative rules) without providing an understanding of the initial concept.This condition has the potential to cause misconceptions, such as the assumption that derivatives are merely a "formula" without geometric or applicative meaning. These findings underscore the importance of evaluating and improving textbooks so they can balance the conceptual, procedural, and representational aspects of learning function derivatives.